Optimization and continuous-flow operation of electrochemically mediated selective formate separation by polyvinyl ferrocene/graphene oxide electrodes - POLAT, SEVGİ (My University, 2023)
Electrochemical carbon dioxide (CO2) reduction is a promising route to convert intermittent renewable energy into fuels and valuable chemical products. Separation of CO2 reduction products by ion-selective electrochemical technology may play a decisive role in the pursuit of commercially viable CO2 reduction processes. Selective separation of formate, one of the main CO2 reduction products, is assessed in the present study in an electrochemical flow cell with symmetric redox-active polyvinyl ferrocene (PVF) functionalized graphene oxide (GO) electrodes. First, experimental parameters such as the PVF/GO ratio, sonication time, and ultrasonic amplitude, were optimized in the electrode preparation process to improve the formate adsorption efficiency on a lab scale (1 × 2 cm electrodes) under static conditions. The electrochemical and morphological characteristics of the electrodes were investigated by cyclic voltammetry and scanning electron microscopy. To demonstrate continuous-flow operation, an electrosorption flow cell (8 × 8 cm) providing inline measurements was constructed. The flow cell results showed selectivity at > 5.5 toward the removal of formate from an electrolyte containing perchlorate at an excess of 30 times the normal value. The performance of the electrosorption cell was also tested using a mixture of methanol, ethanol, formate, and acetaldehyde produced in a CO2 reduction electrolyzer. In this demonstration, formate separation was achieved with a selectivity of > 4.0. The results suggest that the optimized design of the electrochemical cell and operation conditions of the flow platform pave the way for scaling up selective formate separation with PVF/GO electrodes.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, ÇEVRE; MÜHENDİSLİK, KİMYASAL; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, ENVIRONMENTAL; ENGINEERING, CHEMICAL; ENGINEERING, MANUFACTURING; Genel Kimya; Fizik Bilimleri; Çevre Kimyası; Genel Kimya Mühendisliği; Endüstri ve İmalat Mühendisliği; General Chemistry; Physical Sciences; Environmental Chemistry; General Chemical Engineering; Industrial and Manufacturing Engineering; Cell design; Electrochemical separation; Formate; Optimization; Resource recovery